DIGITAL TRANSFORMATION AND INSTITUTIONAL ATTRACTIVENESS IN HIGHER EDUCATION IN UZBEKISTAN: DEVELOPMENT AND APPLICATION OF THE IRSI COMPOSITE INDEX (World Economics and Finance Bulletin, 2026)
This study develops and applies the Integrated Rating of Smart Implementation (IRSI) index to evaluate how digital transformation relates to the attractiveness of higher education institutions in Uzbekistan. Because application-level demand data were not consistently available across institutions, attractiveness was operationalized as a multidimensional institutional outcome combining learning outcomes, learning management system (LMS) engagement, class attendance, test results, and user satisfaction. The study used a six-year institutional panel covering five leading universities from 2020 to 2025 and combined expert-based weighting, survey validation, comparative trend analysis, and exploratory forecasting. IRSI weights were estimated through the Analytic Hierarchy Process using 15 experts, then checked with consistency analysis, Cronbach's alpha, and a 1,000-iteration Monte Carlo simulation. The satisfaction sub-index was derived from a structured survey instrument covering internet quality, infrastructure, staff competence, and content quality, with additional content-validity, constructvalidity, and test-retest checks. The largest weights were assigned to learning outcomes (0.354) and LMS engagement (0.245), while the overall weighting scheme showed acceptable consistency (CR = 0.067) and good reliability (alpha = 0.85). Between 2020 and 2025, all five universities recorded substantial IRSI growth, with 2025 scores ranging from 82 to 93 points. Under the realistic 2030 scenario, the two leading institutions are projected to approach 98 points, while the lowest-ranked institution is projected to reach 91.5 points. The findings suggest that digital transformation in Uzbekistan is associated with stronger educational performance, better user experience, and a more attractive higher education environment, although regional disparities remain visible.
Keywords: Digital transformation; higher education